Bronchial Blocker Provides Hemodynamic stability for One Lung Ventilation in Right Video-Assisted Thoracoscopic Surgery: An Observational Study - Kalam, Farzana; Akter, Suraya; Hussain, Md Pervez Altaf (Journal of the Bangladesh Society of Anaesthesiologists, 2021)
Background: Double lumen endotracheal tubes (DLT) and bronchial Blockers (BB) have been both beenused for lung isolation in video-assisted thoracic surgery (VATS) with some inherent demerits. Objective: The aim of this study was to observe the quality of lung deflation of a bronchial blocker forone lung ventilation & the hemodynamic stability in video-assisted thoracic surgery(VATS). Materials & methods: A total forty adult patients have been assigned to observe the effects & hemodynamicstability of BB who undergoing VATS procedure for mediastinal mass surgery. Correct placement ofairway was confirmed by fiber optic bronchoscopy. The variables assessed were: 1. Time required forcorrect placement of device, 2. Time taken for lung collapse, 3. Quality of Lung collapse, 4. Number oftimes of airway mal-positioned, 5. Changes of blood pressure and heart rate at baseline (T1) and immediatebefore (T2) and after (T3) intubation and one minute after (T4) intubation, 6. Number of patients withhypoxemia (Spo2 <90%) during one lung ventilation, and 7. Post-operative complication like hoarsenessof voice, sore throat and lung infection. Result: Results were observed for MAP & HR at T1, T2, T3 &T4. It was shown that HR decreasedafter induction than the baseline (T1) & came near baseline one min after intubation(T4). Just afterintubation at T3, HR increased from the baseline & immediate before induction (T1&T2). MAP wasalso increased at T3 than T1 & T2. Time taken for right lung collapse with BB was (4.76±0.61) similarand comparable to other studies. Total 36 patients were achieved total collapse of the lung and incidenceof device malposition was observed in case of 5 patients. On the other hand, hypoxaemia was observedin case of 1 patient. Conclusion: Result showed that BB could be a better and effective alternative in VATS Procedureconsidering a longer time to achieve complete lung collapse with minimum hemodynamic changes andwith minimum post-operative complications. JBSA 2021; 34(1): 38-42